KAJIAN PENGENDALIAN PENYAKIT LAYU FUSARIUM DENGAN TRICHODERMA PADA TANAMAN TOMAT - Heriyanto (JURNAL TRITON, 2019)
The study aims to determine the concentration of Trichoderma sp. effective for the control of Fusarium oxysporum wilt in tomato plants, which was carried out in Argodadi Village, Sedayu District, Bantul Regency, from July to November 2018. The study used a completely randomized block design consisting of 5 treatments of the concentration of Trichoderma sp. namely 0.0 g, 2.5 g, 5.0 g, 7.5 g and 10.0 g of biomass with replications 4 times each treatment. The application was carried out by biomass Trichoderma sp. Isolates. Inoculated in 2.5 kg of organic fertilizer / compost, then sprinkled on the land before planting tomato seeds. The results showed that based on the analysis of the incubation period, the percentage of affected plants and the intensity of the attack treatment Trichoderma sp. with a concentration of 10.0 g of biomass, the results were effective in reducing the intensity of Fusarium oxysporum wilt attack by 15.15 percent.